Växthusgasutsläpp vid sandinblandning i torvjordar - Mattsson, Andreas (SLU/Dept. of Soil and Environment, 2018)
Peat soils are organic soils which make up significant parts of Sweden land area. Peat soils are commonly used in agriculture. Growing crops in these soils require drainage which speeds up the degradation of the organic matter and increases the greenhouse gas emissions. Cultivated organic soils are responsible for 6-8 % of the total amount of anthropogenic greenhouse gas emissions in Sweden. Previous studies show a decreased emission flow in peat soils with waste foundry sand mixed in. In this study, sand and waste foundry sand is mixed in with peat in depths of 2,5 cm and 5 cm, respectively and studied in a lab environment where emissions of carbon dioxide, nitrous oxide and methane gas were measured. Results show a noteworthy decrease in carbon dioxide emissions from samples with 5 cm sand/waste foundry sand mixed in. The waste foundry sand raised the pH level in the soil more than sand. This is likely the reason that waste foundry sand performed slightly higher emissions since it improves living conditions for the microorganisms in the soil. Measurements of nitrous oxide and methane gas showed no clear signs of emissions. The measured concentrations were equivalent to those occurring naturally in the lab. The conclusion of this study is that both sand and waste foundry sand can be positive for decreasing the carbon dioxide emissions from peat soils. In order to ensure this result more substantial studies and a deeper knowledge of the processes in the soils is required.